METHODOLOGY OF CREATING STRATEGIC AND INVESTMENT PLANS FOR THE DEVELOPMENT OF EDUCATIONAL INSTITUTIONS - V. Pavlichenko; O. Pavlichenko; O. Borodiyenko; Y. Malykhina (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. The purpose of the article is to substantiate the principles and present the author’s methodology for creating strategic and investment plans for the development of educational institutions.